The study on the Currency Substitution under the background of RMB appreciation - Yang, Ziyu (2012)
Currency substitution is an ineluctable and wild existing financial phenomenon in open economy. It can be essentially understood as the substitution of the functions of domestic currency by foreign currency, and can also be analysed from the aspect of the motive of demand for money. Among all the determinants of currency substitution, the changes in exchange rate have mainly influenced the degree of the currency substitution.